Vermistatin Derivatives with α-Glucosidase Inhibitory Activity from the Mangrove Endophytic Fungus Penicillium sp. HN29-3B1 - Liu, Yayue; Xia, Guoping; Li, Hanxiang; Ma, Lin; Ding, Bo; Lu, Yongjun; He, Lei; Xia, Xuekui; She, Zhigang (Planta Medica, 2014)
Three new vermistatin derivatives, 6-demethylpenisimplicissin (1), 5′-hydroxypenisimplicissin (2), and 2′′-epihydroxydihydrovermistatin (3), along with five known vermistatin analogues, methoxyvermistatin (4), vermistatin (5), 6-demethylvermistatin (6), hydroxyvermistatin (7), and penisimplicissin (8), were isolated from the culture of the mangrove endophytic fungus Penicillium sp. HN29-3B1 from Cerbera manghas. Their structures were elucidated mainly by nuclear magnetic resonance spectroscopy. The absolute configurations of compounds 1 and 2 were deduced on the basis of circular dichroism data. The absolute structures of compounds 3 and 5 were confirmed by a single-crystal X-ray diffraction experiment using Cu Kα radiation. In the bioactivity assay, compounds 1 and 3 exhibited α-glucosidase inhibitory activity with IC50 values of 9.5 ± 1.2 and 8.0 ± 1.5 µM, respectively. The plausible biosynthetic pathways for all compounds are discussed.
Keywords: vermistatin; endophytic fungus; Trichocomaceae; Cerbera manghas; Penicillium sp.; α-glucosidase inhibitory activity